2021
DOI: 10.1111/apa.15822
|View full text |Cite
|
Sign up to set email alerts
|

Mode of delivery was associated with transient changes in the metabolomic profile of neonates

Abstract: Aims: To estimate potential differences in neonatal metabolomic profiles at birth and at the time of newborn screening by delivery mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(92 reference statements)
0
4
0
Order By: Relevance
“… 2 , 4 , 6 , 19 Previously, delivery mode and diet have been shown to induce clear separation in fecal metabolic profiling after birth. 20–22 Consistently, L-carnitine and short-chain acylcarnitines were elevated in C-section or formula-fed newborns compared with the vaginally delivered or breast-fed newborns (Figure S3a-c). However, the differences in distinct fecal aylcarnitines being identified based on delivery mode and diet in early age, were lost when the infants reached 12 months of age (data not shown).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“… 2 , 4 , 6 , 19 Previously, delivery mode and diet have been shown to induce clear separation in fecal metabolic profiling after birth. 20–22 Consistently, L-carnitine and short-chain acylcarnitines were elevated in C-section or formula-fed newborns compared with the vaginally delivered or breast-fed newborns (Figure S3a-c). However, the differences in distinct fecal aylcarnitines being identified based on delivery mode and diet in early age, were lost when the infants reached 12 months of age (data not shown).…”
Section: Resultsmentioning
confidence: 57%
“…Medium- and long-chain acylcarnitines (C10:0, C12:1, and C14:1) were increased at newborn age and remained high even at 4 months only in the vaginally born infants ( Figure 4a , and Table S4-1), suggesting the potential influence of delivery mode on fatty acid oxidation. 20 The accumulation of dicarboxylic fatty acids in the urine of C-section infants also supported the occurring of alternative fatty acid oxidation mechanisms. 24 Vaginally delivered infants have different microbiota composition and functionality from C-section 25 and therefore is expected to have different contribution to the gut metabolome.…”
Section: Resultsmentioning
confidence: 87%
“…One found that low birth weight and extremely macrosomic newborns showed dissimilar metabolomic profiles when compared to appropriate-for-gestational age neonates [ 837 ]. The other estimated potential differences in neonatal metabolomic profiles at birth and at the time of NBS by delivery mode and found small differences, if any, and concluded that the mode of delivery does not affect the results of NBS [ 838 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lack of mediation effects on childhood overweight, for the metabolites mediating the effect of gestational age on rapid growth, paves the way to different interpretations. First, cord blood metabolite concentrations were found to be transient by delivery mode [ 40 ], which could have contributed to a lack of link with childhood overweight. Second, because these cord blood metabolites mediated the effect of gestational age on rapid growth, which was inherent to their selection and rapid growth is a phenotype closer to birth, the studied metabolites may have a role in the origin of metabolic programming that we were not able to capture yet in relation to overweight later in childhood [ 41 ].…”
Section: Discussionmentioning
confidence: 99%